PENGGUNAAN METODE DEMONSTRASI UNTUK PENINGKATAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPA DI SD NEGERI KAWANGKOAN KECAMATAN KALAWAT - Sobon, Kosmas; Lumowa, Sofly Junike (Universitas Nusantara PGRI Kediri, 2018)
The purpose of this research is to increase student activity and learning outcomes in science learning in fifth grade. This research is a classroom action research conducted in two cycles. Each cycle consists of two learning meetings. The subject of this research is the fifth grader at the state elementary school of kawangkoan. Data collection techniques use tests, observations and documentation. The results showed that: (1) student learning activity in first cycle is 72,50% with active criterion and on second cycle is 76,15% with active criterion; (2) mastery of student learning outcomes in first cycle is 71,43% and second cycle is 100%. Based on these results, it can be concluded that by the method of demonstration can improve the quality of learning science subjects, that is: student activity and student learning outcomes of fifth grade state elementary school Kawangkoan. Keywords: demonstration methods, science, learning activity, learning result